The Role of the Nurse in the Treatment of Back Pain - Anna Antczak; Beata Haor; Mariola Głowacka; Monika Biercewicz (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
The development of civilization has led to the increasing prevalence of spinal problems. Lifestyle in the form of long hours of sitting or standing significantly affect the reduction in spinal mobility and promotes complaint back pain. Its structure is closely related to the functioning of the human being. Back pains are varied in terms of pathogenesis uprising. A common feature is pain that occurs in the lumbar area — the cross and the cross — the hip, with varied backgrounds and character. Treatment is based on conservative methods, such as drug treatment and rehabilitation, and surgery. An important role is played by prevention of backaches distributed among learners and workers. This article aims to highlight the role of nurses over patients with spinal pain syndromes in various stages of treatment. The nurse must take care individually and holistically. It is based mainly on alleviating pain and help the patient because of the temporary reduction in physical activity, which impedes the proper functioning. It is aimed at the comprehensive preparation of the patient and his family for self-care. (JNNN 2014;3(1):39–43)